P11.45.B Improved overall survival following Stereotactic Radiosurgery for brain metastases - a single institution experience. (5th September 2022) - May, C; Forshaw, M; Wong, H; Brass, R; Corns, A; Shenoy, A; Mehta, S
Abstract: Background: Brain metastases are increasingly common due to longer survival associated with advancements in treatment. Approximately 40% of cancer patients are diagnosed with brain metastases at some point during their disease. Stereotactic radiosurgery (SRS) avoids the neuro-cognitive toxicity associated with whole brain radiotherapy and has been increasingly offered as a treatment alternative for brain metastases. Combined with developments in systemic treatments, this approach has resulted in improved overall survival (OS). This study reviewed patients treated with single fraction SRS at our institution with a primary endpoint of overall survival. Material and Methods: A retrospective review determined overall survival for 237 patients who received single fraction SRS for 451 brain metastases from solid tumours between 1 st January 2017 and 31 st December 2021. Primary tumour sites were classified as breast, kidney, colorectal, melanoma, lung or other. SPSS v.27 was used for Kaplan Meier OS determination. The median follow up was 10.3 months. Cox regression analysis assessed the association between Gross Tumour Volume (GTV) and OS. Results: In this patient cohort, 60% (N=142) were female and 40% (N=95) were male, with a median age of 63 [32-85]. 63.7% (N = 151) had a solitary metastasis. Patients received a single fraction of 15, 17.5 or 20 Gy (prescribed to 80% isodose) dependent on the planning target volume (PTV) size and whether it was initial treatment or re-treatment. 71% of all patients were alive at 6 months with median OS of 12.0 months [10.6-13.4]. Primary tumour site significantly affected OS (Log rank, Chi squared 15.656, p0.008) with breast cancer patients (N=58) surviving longest with a median OS 16.0 months [13.6-18.4] followed by melanoma median OS 15.0 months [7.6-22.4], kidney cancer patients (N = 24) median OS 12.0 months [8.3-15.7] and lung patients (N=87) median OS 10.0 months [8.9-11.3]. The lowest median OS was for colorectal patients at 7.0 months [1.4-12.6]. However, considering the small sample size, N = 15, more data is needed to confirm the significance. The larger the GTV volume the lower the survival time (Chi squared 8.692, p 0.003). Conclusion: 71% of patients had an OS of 6.0 months or more with a median of 12.0 months. As expected, primary tumour site has a significant impact on OS, with breast cancer patients living longest. In addition, increasing GTV size is associated with significantly worse survival. Given the improved survival for these patients, the avoidance of neuro cognitive decline remains of paramount importance and outcomes for these patients need to be reported in future work.